Pemahaman Mahasiswa Akuntansi tentang Makna Konvergensi IFRS di Indonesia (Studi Kasus pada PT yang sudah terakreditasi A di kota Semarang) - Ernawati Budi Astuti (AKSES: Jurnal Ekonomi dan Bisnis, 2014)
The convergence process with the development and adoption of International Financial Reporting Standards (IFRS) as national standards has become the focus of governments, professionals and researchers. The growing number of countries implementing IFRS, their experiences and emerging challenges have further raised researchers’ attention. This research examine the comprehension of students in university about IFRS convergence process in Indonesia and find factors that shape that level of comprehension. This research object are students in university that had accredited in level A, who had taken subject Accounting Theory and International Accounting. Relating to research, it explains how and why research can provide meaningful input into accounting curriculum development, and identifies questions that can motivate research related to topics on the education world.Keywords: IFRS, comprehension, accounting curriculum